Dental malpractice and related cases in the Philippines - Mirabueno, Maria Edna
This study consists mainly of analysis of recorded cases filed against dental practitioners in the Professional Regulation Commission with the following objectives: To determine the nature and number of dental malpractice cases commonly submitted to the PRC through the Board of Dentistry, the number of resolved and unresolved cases, the problems encountered in the resolution of cases, the possible social political, economic and cultural implication of cases and to recommend possible remedial measures which could be instituted or adjusted to prevent dental malpractice.